Specialty Payment Model Opportunities and Assessment Gastroenterology and Cardiology Model Design Report - Mulcahy, Andrew W. (RAND Corporation, 2015)
Gastroenterology and cardiology services are common and costly among Medicare beneficiaries. Episode-based payment models may offer a way to create incentives for high-quality, low-cost care. This report describes research related to the design of episode-based payment models for ambulatory gastroenterology and cardiology services for possible testing by the Centers for Medicare and Medicaid Services' Center for Medicare and Medicaid Innovation.